Poles Apart: Where and How Cells Construct Nisin - Hill, Colin (mBio, 2020)
Nisin is a 34-amino-acid lantibiotic that has been used commercially for almost a century as a food preservative. In order to produce active nisin, Lactococcus lactis requires an 11-gene operon that encodes proteins involved in modification, processing, transport, immunity, and regulation. While the role of each of the 11 proteins is well understood, the location and spatial organization of the biosynthetic machinery that involves NisA, NisB, NisC, NisT, and NisP remain to be determined. In this elegant paper (J. Chen, A. J. van Heel, and O. P. Kuipers, mBio 11:e02825-20, 2020, https://doi.org/10.1128/mBio.02825-20), we learn that a NisB dimer is recruited to the “old” pole of a dividing cell, where it assembles with NisC to form a modification complex that can engage with NisA. Unexpectedly, the NisT transporter does not stably assemble into this complex but is distributed around the membrane until it engages with the NisABC complex to transport NisA across the membrane, whereupon it dissociates from NisBC.